Effect of Dietary Supplementation of Mannan Oligosaccharides and Acidifier Calcium Propionate on the Performance and Carcass Quality of Japanese Quail (Coturnix japonica) - Bonos, Eleftherios M.; Christaki, Efterpi V.; Florou-Paneri, Panagiota C. (International Journal of Poultry Science, 2010)
The effect of the dietary supplementation of Mannan Oligosaccharides (MOS) and the acidifier Calcium Propionate (CP) on the performance and carcass quality of the Japanese quail (Coturnix japonica) was investigated in this experimentation. Three hundred, one-day old Japanese quail divided into four groups with three subgroups each were fed a basal diet that served as control, or a basal diet containing 6 g/kg CP, or 1 g/kg MOS or 1 g/kg MOS plus 6 g/kg CP. The body weight, feed consumption, feed conversion ratio and mortality of the birds were calculated at weekly intervals. On last day of the growing period (day 42) the birds were slaughtered, the carcasses were processed and the carcass weight, carcass dressing percentage and carcass parts percentage were calculated. Furthermore, the breast meat composition and its fatty acid profile were analyzed. The results of the experimentation showed that the addition of MOS in the feed of growing quail significantly (p<0.050) increased the body weight on second week and the feed consumption on second and fourth weeks, while it decreased the liver to live weight percentage and the palmitic acid content of the breast meat. Moreover, the addition of CP in the feed significantly (p<0.050) decreased the feed consumption on fifth week and the heart to live weight percentage. Significant (p<0.050) interaction between the examined supplements was observed on the feed consumption, the FCR and the liver to live weight percentage. No adverse effects from the dietary addition of MOS or CP or both were observed on the performance or the carcass quality of the growing quail.